Rethinking Science Communication: The Need for Dialogic, Transdisciplinary Collaboration - Julia Kiernan (Journal of the Assembly for Expanded Perspectives on Learning, 2023)
Rethinking Science Communication: The Need for Dialogic, Transdisciplinary Collaboration